2013
DOI: 10.1155/2013/194927
|View full text |Cite
|
Sign up to set email alerts
|

Clozapine Use Presenting with Pseudopheochromocytoma in a Schizophrenic Patient: A Case Report

Abstract: Introduction. There have been six previous cases that reported pseudopheochromocytoma in patients taking clozapine. Our case showed the direct link of clozapine to serum levels of certain markers. Case. This is a case of a 49-year-old obese Caucasian female who was referred to endocrinology for investigation of Cushing's syndrome, based on raised blood pressure and Cushingoid facies. The patient had underlying schizophrenia and was stable on clozapine. Her blood pressure was 150/99 mmHg on bendroflumethiazide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…The hypertension was accompanied by rise in urinary E and NE, to which all 3 anomalies subsided after interventions were introduced and CLZ was discontinued (Li et al, 1997 ). Paroxysmal hypertension was diagnosed, as with multiple other case reports of CLZ-associated hypertension and raised urinary catecholamines (Krentz et al, 2001 ; Akinsola and Ong, 2011 ; Sara et al, 2013 ). In addition to hypertension, Akinsola and Ong ( 2011 ) reported tachycardia of 140 bpm in a patient and Krentz et al ( 2001 ) reported 3 cases of accelerated HR ranging from 104 to 130 bpm.…”
Section: Resultsmentioning
confidence: 69%
See 2 more Smart Citations
“…The hypertension was accompanied by rise in urinary E and NE, to which all 3 anomalies subsided after interventions were introduced and CLZ was discontinued (Li et al, 1997 ). Paroxysmal hypertension was diagnosed, as with multiple other case reports of CLZ-associated hypertension and raised urinary catecholamines (Krentz et al, 2001 ; Akinsola and Ong, 2011 ; Sara et al, 2013 ). In addition to hypertension, Akinsola and Ong ( 2011 ) reported tachycardia of 140 bpm in a patient and Krentz et al ( 2001 ) reported 3 cases of accelerated HR ranging from 104 to 130 bpm.…”
Section: Resultsmentioning
confidence: 69%
“…In addition to hypertension, Akinsola and Ong ( 2011 ) reported tachycardia of 140 bpm in a patient and Krentz et al ( 2001 ) reported 3 cases of accelerated HR ranging from 104 to 130 bpm. The authors postulated CLZ-induced paroxysmal hypertension arose from the increase in NE spillover due to reduced reuptake into sympathetic nerve endings, α-adrenoceptor antagonism and/or increased vesicular fusion (Li et al, 1997 ; Krentz et al, 2001 ; Akinsola and Ong, 2011 ; Sara et al, 2013 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As was true for our case, the cases of clozapine-induced hypertension have been reported among males only, aged 32–49 years,[ 3 4 5 6 7 ] who had no history of hypertension in the past. [ 3 4 6 7 ] However, the onset of hypertension during clozapine initiation was associated with other abnormalities such as myocarditis,[ 11 12 13 ] pseudopheochromocytoma,[ 14 15 16 17 ] and hypokalemia. [ 7 ] Hence, whenever a patient develops hypertension with use of clozapine, it is important to thoroughly evaluate for other possible causes, which could contribute or lead to hypertension.…”
Section: Discussionmentioning
confidence: 99%